Motion based gesture detection using frame composition LSTM - Islam, Ishraqul; Islam, Md. Saqif; Provat, Mahin Islam; Khandakar, Shaneen Shadman; Karim, Fardin Junayed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.